2006
DOI: 10.1007/s00535-005-1686-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cilostazol, a selective type-III phosphodiesterase inhibitor, on water-immersion stress-induced gastric mucosal injury in rats

Abstract: In this study, we demonstrated that a selective type-III phosphodiesterase inhibitor, cilostazol, inhibited stress-induced gastric inflammation and damage via suppressing the production of pro-inflammatory cytokines. Cilostazol may be useful for preventing gastric mucosal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
4
10
1
Order By: Relevance
“…PTX decreased the levels of TNF-α and IL-1β significantly in EtOH-induced ulcerated gastric mucosa, and the above observation is in confirmation with the reported work of other workers. [2,23,24] TNF-α is reported to stimulate the upregulation of IL-1β levels, so by controlling the TNF-α expression, the IL-1β expression can be controlled. This may be the mechanism by which PTX decreases both the cytokines levels.…”
Section: Discussionmentioning
confidence: 99%
“…PTX decreased the levels of TNF-α and IL-1β significantly in EtOH-induced ulcerated gastric mucosa, and the above observation is in confirmation with the reported work of other workers. [2,23,24] TNF-α is reported to stimulate the upregulation of IL-1β levels, so by controlling the TNF-α expression, the IL-1β expression can be controlled. This may be the mechanism by which PTX decreases both the cytokines levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cilostazol has been reported to inhibit endothelial-neutrophil adhesion by decreasing adhesion molecules expression [12,13]. In the previous study, we reported that cilostazol reduces gastric mucosal lesions induced by water-immersion stress by reducing proinflammatory cytokine production in the gastric mucosa [14].…”
Section: Introductionmentioning
confidence: 98%
“…A recent randomized, crossover study of healthy CYP2C19 * 1/ * 1 subjects (n = 160) also demonstrated that the effect of omeprazole on the plasma concentration and antiplatelet actions of clopidogrel appears to be greater than that of lansoprazole 6) . The results of the present study including stented patients highlight the significant interaction between lansoprazole and clopidogrel, although the observed stress-induced gastric mucosal inflammation and injury by suppressing the production of pro-inflammatory cytokines in rats 35,36) . In contrast to aspirin and thienopyridine, cilostazol does not significantly prolong the bleeding time; this property remains even when cilostazol is added to other antiplatelet regimens 37) .…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, clopidogrel does not have a direct effect on the gastric mucosa, but rather inhibits the healing process of gastric mucosal injury induced by aspirin. In contrast to that observed with aspirin and clopidogrel, several experimental studies have shown the beneficial effects of cilostazol on gastric mucosal damage and/or bleeding [34][35][36][37] . Compared with aspirin, cilostazol significantly ameliorated microcirculatory and villous damage to the intestinal mucosa following ischemia-reperfusion injury in a mice study 34) .…”
Section: Discussionmentioning
confidence: 78%